2015
DOI: 10.1074/jbc.m114.609222
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Human Erythrocytic Bioactivation of Nitrite

Abstract: Background: Erythrocytes contribute to nitrite-mediated NO signaling, but the mechanism is unclear. Results: Deoxyhemoglobin accounts for virtually all NO made from nitrite by erythrocytes with no contributions from other proposed pathways. Conclusion: Deoxyhemoglobin is the primary erythrocytic nitrite reductase operating under physiological conditions. Significance: Reduction by deoxyhemoglobin accounts for nitrite-mediated NO signaling in blood mediating vessel tone and platelet function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
81
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 70 publications
(86 citation statements)
references
References 47 publications
4
81
0
Order By: Relevance
“…5B). The observed changes in platelet activation by human RBCs and nitrite are significant (P = 0.038) and consistent with previous results (11) (Fig. S4).…”
Section: Resultssupporting
confidence: 92%
See 4 more Smart Citations
“…5B). The observed changes in platelet activation by human RBCs and nitrite are significant (P = 0.038) and consistent with previous results (11) (Fig. S4).…”
Section: Resultssupporting
confidence: 92%
“…5). We observed that nitrite inhibits platelet activation in the presence of human deoxyHb as previously reported (11,13) (Fig. 5A).…”
Section: Resultssupporting
confidence: 89%
See 3 more Smart Citations